Synthesis and Antifungal Activity Against of Candida Species for Some New Heterocyclic Compounds Containing Schiff Base , Oxazepine , Indoline or Imidazolo Units and Their Spectral Characterization - AL-khazraji, Shaima Ibraheem chyad; Mohammed, Bari L.; AL-Salihi, Siham Sh. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
The objective of this study is to test In Vitro the twenty chemical compounds that contains Schiff base or oxazepine, indoline, imidazolo units in concentrations( 50, 100, 150) mg / dl as antifungal activity, against three pathogenic Candida species  that occur in humans. We tested one isolates of   ) Candida albicans ,Candida glabrata and Candida krusei). All these species affect human health . The study was carried out in the Laboratory of Public Health , directly of health for the period from May 2016 to April 2017  , Candida spp isolates used in this study were collected from patients admitted at  some private clinical in  Kirkuk city . All isolates were identified using CHROM agar and stored at -70 0C. Preparation of Schiff base ( 1-7 ) from amino pyridine derivatives with aromatic aldehyde by nucleophilic addition reactions preparation of 1,3 â€“ oxazepine 4,7 â€“ dione ( 8-13 ) were carried out by cyclization of appropriate Schiff bases with malic anhydride and phthalic anhydride , preparation of compounds ( 14 â€“ 17) from reaction of a mixture aminopyridine derivative with potassium hydroxide then chloroacetic acid was  added , preparation of compounds ( 18 â€“ 20 ) from reaction of amino pyridine derivative and 4- phenyl phenacyl bromide , all these compounds were characterized by melting points and FT.IR spectroscopy. Some of them were characterized by H1- NMR and C13-NMR spectroscopy .Some compounds contain Schiff base  group in compounds( 1-7) showed inhibitory effect Candida albicans and Candida krusei  .This study demonstrates that the three Candida species were resistant to a range of compounds (8-13) containing oxazepine and as antifungal against , while the compound(14-17) contain Indolin show low inhabition zon for Candida albicans and the compound (18-20) contain imidazo group showed inhibited  effect against three Candida species.